Analyzing Students’ Acceptance Toward the Use of Tutorial Webinar Using Technology Acceptance Model Approach - Binti Muflikah; Vica Ananta Kusuma; Swidarto Swidarto; Sari Famularsih (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to describe and analyze the acceptance of Universitas Terbuka (UT) students in using the Microsoft Teams and Learning Management System (LMS) applications for the Webinar Tutorial (Tuweb) during the COVID-19 pandemic. Method: This research used an explanatory approach. The population of this study was 4000 students of the Distance Learning Program Unit (UPBJJ) at Universitas Terbuka Semarang. Meanwhile, the research sample was 1600 students in Rembang, Blora, Pati, Kudus, Jepara, Demak, Semarang, Kendal, Kaliwungu, and Pekalongan teaching units. The data was collected through questionnaires, interviews, and documentation. Results: The results showed that the acceptance of Universitas Terbuka students in using the Microsoft Teams application for Tuweb obtained an average of 82.76 in the accepted category, with a contribution of 63.50%. In comparison, student acceptance using the LMS application obtained an average of 81.58 in the accepted category, with a contribution of 80.40% from other dimensions. Novelty: The result showed that the students' acceptance of using Tuweb, both Microsoft Teams or LMS applications, indicates that these learning aids can be used as an alternative for teaching and learning besides face-to-face meetings.